The Translation Technique of Nouns Representing the Participants in the Subtitle Translation Film "The Conjuring 2: The Enfield Poltergeist" - Megan Asri Humaira, Rasmitadila , Rusi Rusmiati Aliyyah , Muhamad Aminulloh; Achmad Samsudin (International Journal of Advanced Science and Technology, 2020)
The purpose of this research is to know the translation techniques performed in translating nouns representing participants. In conducting research used qualitative methods with the technique of content analysis. With the data referred to, the clauses, in particular, are nouns. The results of this study showed that the translation technique literally dominated by a percentage of 49.5% compared to the use of other translation techniques. The translation also follows its target language so that the content of the story or meaning conveyed by the source text can be understood.